Features of allometric growth and structure of settlements for Mya uzenensis (Bivalvia: Myidae) in different areas of littoral zone in the Tauiskaya Guba Bay, Okhotsk Sea - V. S. Zharnikov (Известия ТИНРО)
Settlements of bivalve Mya uzenensis are investigated in four littoral areas of the Tauiskaya Guba Bay with different environments. Their density varied from 20 to 194 ind./m2 (518–9680 g/m2) depending on habitat. On suitable soils, the settlements occupied 25–40 % of the littoral zone; the mollusks were distributed mostly in mosaic spots with size 0.5–5.0 m2. Stable settlements in the areas with favorable environmental conditions in the Ola estuary and Vesyolaya Bay were formed by mollusks with shell size of 22.1–91.1 mm and age of 2–14 years. Allometry of the shells growth increased with age until 10 years, then leveled. The stocks of mollusk were assessed for certain areas that allowed to recommend for annual landing 158.4 t of M. uzenensis (7 % of commercial stock).